An AGB Star with a Thick Circumstellar Shell. (13th March 2020) - Mould, Jeremy; Durré, Mark; Uddin, Syed; Wang, Lifan
Abstract: The Asymptotic Giant Branch is the terminal phase of red giant evolution with timescales of millions of years and a total mass lost from the star that is a significant fraction of the initial mass. Investigation of one of these stars, WISEA J173046.10–344455.5, a kpc in the direction of the center of the Galaxy, reveals a cool oxygen rich star with a dust shell of blackbody temperature 1305 K.